Formation of functional indicators of meat slaughtered animals - Strashynskyi, Igor; Pasichnyi, Vasyl; Shevchenko, Tatiana; Karapalov, Anton (My University, 2021)
The actual tasks facing the meat industry are the rational use of meat raw materials with different technological characteristics and improving the quality of products that are produced. Today, in the world market of meat raw materials widely distributed meat with impaired progress autolysis. The results of monitoring the quality indicators of pork, which are processed at LLC "Ternopil meat processing plant", and the study of the impact of pre-slaughter and technological factors on the quality of meat raw material obtained from slaughtering pigs from different farms, are presented in the article. Актуальними завданнями, що стоять перед м’ясною промисловістю, є раціональне використання м’ясної сировини з різними технологічними характеристиками та підвищення якості продукції, що виробляється. Сьогодні на світовому ринку м'ясної сировини широко поширене м'ясо з порушенням ходу автолізу. Результати моніторингу показників якості свинини, яка переробляється на ТОВ «Тернопільський м’ясокомбінат», та вивчення впливу передзабійних і технологічних факторів на якість м’ясної сировини, отриманої від забійних свиней різних господарств, представлені в статті.
Keywords: кафедра технології м’яса і м’ясних продуктів; functional and technological properties; pork meat; autolysis; pH; quality; exposure before slaughter; функціонально-технологічні властивості; м'ясо свинини; автоліз; якість; експозиція до забою